2007
DOI: 10.1016/j.pacfin.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Executive compensation, firm performance, and Chaebols in Korea: Evidence from new panel data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 46 publications
7
61
0
3
Order By: Relevance
“…However, the results are in line with the results of Bussin and Blair (2015), Conyon (1997), Conyon et al (2000), Coughlan and Schmidt (1985), Fatemi et al (2003), Gabaix and Landier (2008), Kato et al (2007), Masson (1971), Murphy (1985) and Scholtz and Smit (2013). The link between executive director remuneration and share performance may be an indication that remuneration policies are based on the share price (or market capitalisation) and is thus directly connected to the principle of shareholder wealth maximisation.…”
Section: Resultssupporting
confidence: 89%
“…However, the results are in line with the results of Bussin and Blair (2015), Conyon (1997), Conyon et al (2000), Coughlan and Schmidt (1985), Fatemi et al (2003), Gabaix and Landier (2008), Kato et al (2007), Masson (1971), Murphy (1985) and Scholtz and Smit (2013). The link between executive director remuneration and share performance may be an indication that remuneration policies are based on the share price (or market capitalisation) and is thus directly connected to the principle of shareholder wealth maximisation.…”
Section: Resultssupporting
confidence: 89%
“…While the U.S. has required detailed disclosure of executive pay since the 1930s, most other countries have historically required at most the disclosure of aggregate cash compensation for all top executives combined, with no individual data and little information on other pay components . For most countries, this forced researchers to rely on industry surveys (Abowd and Boggano, 1995;Abowd and Kaplan, 1999;Murphy, 1999;Kato and Kubo, 2006;Thomas, 2009;Fabbri and Marin, 2015), to focus on only the cash component of pay (Kato and Rockel, 1992;Conyon and Schwalbach, 2000;Kato and Long, 2006;Kato, Kim, and Lee, 2007), or to examine the combined pay of the entire management team (Kaplan, 1994;Elson and Goldberg, 2003;Bryan, Nash, and Patel, 2006;Muslu, 2010). Notable exceptions with better disclosure are Canada and the U.K., which have required detailed pay disclosures since 1993 and 1995, respectively.…”
Section: International Evidencementioning
confidence: 99%
“…This extends our understanding of the governance roles of executive compensation beyond the confines of agency framework. Research in other Asian countries have also shown stakeholder influence on executive pay in South Korea (Kato, Kim, & Lee, 2005) or the importance of relationship and network influences in China (Firth, Fung, & Rui, 2006;Kato & Long, 2006), even despite newer elements of ''stock market capitalism'' after the Chinese economic reforms. Buck, Liu & Skovoroda (2008: 4) suggest that "Chinese institutions (including culture as an informal institution) may have inhibited the adoption of long-term incentives in the form of equity-based pay, and thus reduced the responsiveness of pay to share price performance.…”
Section: Executive Compensation Debates and Informal Institutionsmentioning
confidence: 99%